LE PROGRAMME DE MONITEURS: SON APPORT AU DÉVELOPPEMENT DU BILINGUISME AU CANADA - Buteau, Magdelhayne F. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1978)
A monitor is a full-time university student who earns by competition the additional part-time employment, under the direction of a teacher of second languages, of assisting in conversational skills those who have already acquired some knowledge of his or her language. The program, sponsored by the federal government for both French and English as second languages, has been in operation for some two or three years in universities across Canada. Buteau explores its history and manner of operation and discusses its intrinsic pedagogical advantages, conspicuous among which is the element of live illustration, afforded by the actions and personality of the monitor, of the other culture in which the second language is embedded.